Extraction of anthocyanins from purple sweet potato: evaluation of anti-inflammatory effects in a rheumatoid arthritis animal model, mechanistic studies on inflammatory cells, and development of exosome-based delivery for enhanced targeting - Dong, Jingjian; Lv, Yuntao; Zhao, Cailiang; Shi, Yuanrui; Tang, Ruiming; He, Liheng; Fan, Ruiwen; Jia, Xiaoyun (Frontiers in Immunology, 2025)
ObjectiveRheumatoid arthritis (RA) is a chronic autoimmune disease marked by inflammation and joint damage. Anthocyanins, such as those from purple sweet potato are known for their anti-inflammatory effects.MethodsThis study evaluated purple sweet potato anthocyanins (PSPA) therapeutic potential in RA using Human RA cells (MH7A) and collagen-induced arthritis (CIA) rat models. Rats were divided into control, CIA model, and three PSPA treatment groups (10, 20, 40 mg/kg) for 14 days. Meanwhile, exosomes were extracted from MH7A cells and loaded with PSPA, then co-incubated with inflammatory cells to observe the targeting capability of the drug-loaded exosomes.ResultsPSPA significantly reduced joint swelling and structural damage in CIA rats, with the highest dose (40 mg/kg) reducing tissue hyperplasia and inflammatory infiltration. PSPA also altered the gut microbiota, increasing beneficial bacteria like Akkermansia and Lactobacillus. Molecular analysis showed reduced serum levels of inflammatory cytokines TNF-α, IL-1β, and rheumatoid factor (RF). In MH7A cells, PSPA decreased inflammatory cytokines (IL-1α, IL-6, IL-18), inhibited cell proliferation (IC50 = 1.43 μg/mL), and induced apoptosis by modulating Bcl-2, Bax, Caspase-3, and Caspase-9. PSPA also restored the PI3K/AKT signaling pathway, reversing the suppression seen in CIA models, particularly at 40 mg/kg. Flow cytometry and microscopy confirmed dose-dependent apoptosis and cell cycle modulation. Meanwhile the PSPA-loaded exosomes demonstrated a high targeting capability toward inflammatory cells.ConclusionThese findings indicate that PSPA can alleviate RA symptoms by reducing inflammation, modulating gut microbiota, and promoting apoptosis in synovial fibroblasts, with exosome-encapsulated anthocyanins enhancing its targeting efficiency.